2022
DOI: 10.1155/2022/7875068
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Effect of Acupuncture and Pressing of Traditional Chinese Medicine on Recovery of Delayed Muscle Soreness in Athletes

Abstract: In this study, we have analyzed numerous effects of the acupuncture and pressing of traditional Chinese medicine on recovery of delayed muscle soreness in athletes. To implement this idea, a total of 84 athletes with delayed muscle soreness treated in our hospital from January 2018 to June 2020 were included. According to the random number table method, they were divided into the experimental group and the control group: among them, 42 cases were in the experimental group and were treated by TCM acupuncture. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%